Translation Criticism: Implementation of House’s TQA Model on “Sweet Hour of Prayer” into Indonesian - Simon Ntamwana; Aris Munandar (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
The article examined the quality of the translation of the hymn “Sweet Hour of Prayer” (1845) into the Indonesian lyric “Inilah Jam Ku Berdoa”. The study used a qualitative method with an inductive orientation. The primary data were collected from the American Seventh-day Adventist Hymnal (1985) and the Indonesian hymnal Lagu Sion (2013). The secondary data were obtained from books and articles about Translation Quality Assessment (TQA), systemic functional linguistics, and SDA hymnody. House’s TQA model was implemented by assessing overt and covert translation errors and by analyzing the profiles of the source and target texts. It was found that the textual profile and function of the target text (TT) do not match those of the source text (ST). Furthermore, it was discovered that the translation of “Sweet Hour of Prayer” from English to Indonesian was not adequate in quality due to manipulations that reduced the lyric to a covert version.